The Influence of Corporate Culture on Firm Value: A Systematic Literature Review - Mila Failasufa; Rela Sari (BUGIS : Journal of Business, Technology, & Social Science, 2026)
This study aims to synthesize empirical evidence on the influence of corporate culture on firm value using a Systematic Literature Review (SLR) method with the PRISMA protocol. A total of 21 reputable journal articles published between 2019 and 2026 were analyzed. The results show that corporate culture generally has a positive impact on firm value through increased innovation, investment efficiency, crisis stability, integrity, ESG transparency, collectivism, and stock liquidity. However, negative effects are found in rigid hierarchical cultures and certain local contexts. The Resource-Based View emerges as the dominant theoretical framework (38%). The study concludes that corporate culture is a strategic asset in value creation, whose effectiveness depends on the alignment between cultural type, organizational life cycle, and local context.